Forage Characteristics of Bermudagrass Pastures Overseeded with Pintoi Peanut and Grazed at Different Stubble Heights - Sanchez, Joao M. D.; Vendramini, Joao M. B.; Sollenberger, Lynn E.; Silveira, Maria L.; Dubeux Jr, Jose C. B.; Moriel, Philipe; Kuwahara, Frank A. [UNESP]; Cecato, Ulysses; Yarborough, James K.; Soares Filho, Cecilio [UNESP]; Leite de Oliveira, Fabio C. (Crop Science Soc Amer, 2018)
Overseeding warm-season legumes into warmseason perennial grass pastures may increase productivity and nutritive value of pastures in tropical and subtropical regions. The objective of this study was to investigate the effects of overseeding 'Amarillo' pintoi peanut (Arachis pintoi Krapov. & W.C. Greg.) into Jiggs bermudagrass [Cynodon dactylon (L.) Pers.] pastures grazed at different stubble heights. The experiment was conducted in Ona, FL, from June to October in 2014 and 2015. Treatments were a split-plot design of two sward types (bermudagrass monocultures or overseeded with pintoi peanut, main plots) and two postgrazing stubble heights (15 or 25 cm [SH15 and SH25], subplots) arranged in a randomized complete block design with four replicates. Pastures were mob stocked, with 28-d resting periods between grazing events. There was no effect of stubble height on pintoi peanut plant density (5.8 plants m(-2)), ground cover (5.8%), or proportion in the herbage mass (HM, 5.2%); however, proportion in the HM increased from 1.1 to 8.2% over 2 yr. There was no effect of sward type on weed ground cover; however, SH25 had greater weed ground cover than SH15 (53.4 vs. 18.2%). Herbage accumulation rate, crude protein, and in vitro digestible organic matter were not affected by sward type (23.4 kg ha(-1) d(-1), 101 g kg(-1), and 431 g kg(-1), respectively). Pintoi peanut proportion in the HM increased over time; however, it may take > 2 yr to have a significant presence of pintoi peanut in the mixed sward.